AN EVALUATION ON PRESCRIBING PATTERN OF ANTIBIOTICS IN PAEDIATRIC INPATIENTS AT TERTIARY CARE HOSPITAL - SABISHRUTHI S,; KAVITHA S,; JAGAN NATHAN B,; KALICHETI PRIYANKA,; ARSHATH A, (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Our objective of the study was to evaluate the prescribing patterns of drugs with cost analysis in pediatric inpatients at tertiary care hospital. Methods: It is an observational prospective study carried out in pediatric inpatients with a sample of 180 patients based on age, inclusion, and exclusion criteria for period of 3 months. The patient’s data were collected using patient case record form and analysis of the data was done. Results: Of 180 patients data were collected, the results show that majority of gender admitted in the hospital were male children 94 (52%) and many are from age group of early childhood (2–5 years) 67 (37%). Respiratory tract infections are diagnosis most commonly analyzed and off overall 236 prescribed antibiotics cephalosporins 86 (43%) and combination of amoxicillin + clavulanic acid 25 (71%) is the class of antibiotics prescribed higher than other class of drugs. Parental 173 (73%) route of administration was observed to be followed more than other route. The percentage of cost variation of antibiotics observed in the study reveals that the huge variations were seen in the cost of medication in maximum and minimum cost. Conclusion: The present study reveals that the prescribed antibiotics were as per the diagnosis of the patient and not by proceeding proper culture sensitivity testing. Hence, awareness about antibiotic must be created among practicing physicians to increase the therapeutic compliance of the patient.